Creutzfeldt–Jakob Disease with Stroke-Like Symptoms: Case report - Tosunoğlu, Bünyamin; Dilek, Sıddıka Sena; Emektar, Ümmühanı; Yoldaş, Tahir Kurtuluş (Acta medica Lituanica, 2022)
Creutzfeldt–Jakob disease (CJD) is a rare, progressive, and fatal prion disease. Often the first sign of CJD is rapidly progressive dementia, leading to memory loss, personality changes, and hallucinations. Myoclonus typically occurs in 90% of cases, but often may not be an initial symptom. Other frequently occurring psychiatric symptoms include depression, anxiety, paranoia, obsessive-compulsive symptoms, and psychosis. Speech disorder, loss of balance and coordination may also accompany. We present a case of CJD with sudden onset of right hemiparesis.